First record of the genus Phanerotomella (Hymenoptera: Braconidae) from Baltic amber with the description of a new species - Kittel, Rebecca N. (Zootaxa, 2018)
A new but exinct chelonine wasp species, Phanerotomella brevivena Kittel sp. nov. (Braconidae: Cheloninae) of the modern genus Phanerotomella is described from Baltic amber. This new species differs from all other extant Phanerotomella species by having the fore wing vein SR-1 only partially sclerotised. This is the first fossil record of the genus in amber.